Penerapan Variasi Teknik Patchwork Pada Ready To Wear Dengan Tema Exotic Dramatic Menggunakan Look Harajuku - Ariyana Damayanti; Dhea Savira Chairunnissa (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Patchwork is made by combining scrap cloth or patchwork with certain patterns or stitches, the writer used patchwork technique in creating ready to wear. The purposes of this technique is thus a writer researches and develops patchwork technique variations for finding out the results of the final result of applying a variety of patchwork techniques on ready to wear. The first method that was used in this research is R&D, a writer did research and development for producing the new products and improving existing products, and test the effectiveness' products. Those two finals of analysis data which is the results for determining the effect of applying patchwork techniques on ready to wear fashion. Those are the final results of three patchwork techniques that were generated by the author such as honeycomb, somerset patchwork, and cathedral window patchwork. The results of those three handicrafts were different, the honeycomb had neatly arranged hexagonal pieces and somerset had a star shape, and the cathedral window looked like a very beautiful window and was made by using folded piece of cloth then sewn neatly.